Intratumor heterogeneity in epigenetic patterns. (August 2018) - Assenov, Yassen; Brocks, David; Gerhäuser, Clarissa
Abstract: Analogous to life on earth, tumor cells evolve through space and time and adapt to different micro-environmental conditions. As a result, tumors are composed of millions of genetically diversified cells at the time of diagnosis. Profiling these variants contributes to understanding tumors' clonal origins and might help to better understand response to therapy. However, even genetically homogenous cell populations show remarkable diversity in their response to different environmental stimuli, suggesting that genetic heterogeneity does not explain the full spectrum of tumor plasticity. Understanding epigenetic diversity across cancer cells provides important additional information about the functional state of subclones and therefore allows better understanding of tumor evolution and resistance to current therapies.